Explicit bias among fourth-year medical students. Issue 1 (2nd January 2019) - Harrison, Leila E.; White, Bobbie Ann A.; Hawrylak, Kaitlyn; McIntosh, David
Abstract: The aim of this study was to analyze themes related to explicit bias in patient-doctor relationships among fourth-year medical students. Class cohorts between 2013 and 2016 taking an online elective, "Self and Culture, " submitted reflections about explicit bias. Thematic analysis was conducted on 283 student submissions totaling 849 entries until saturation. Themes included explicit bias toward patients with obesity, those who smoked, those from low-socioeconomic conditions, and, to a lesser extent, race/ethnicity. Themes related to the patient-doctor relationship included a negative impact on the relationship itself, trust, treatment of the patient, and patient experience. Themes related to making a positive impact included seeking positive treatment of the patient, understanding patients' circumstances rather than making assumptions, partnering with the patient, and education. Furthermore, researchers noted external versus internal attribution of the bias. Some students used neutral language to explain explicit biases, whereas fewer used internal attribution language. Results demonstrated that this type of reflection promoted personal insight, and faculty members should be trained to ensure successful crucial conversations about the impact of assumptions and biases on patient treatment, care plans, and health disparities. Finally, the curriculum should be intentional, providing experiences with marginalized populations to develop cultural humility and empathy.